Unfair contract terms: The case of JYJ v SME - Mohd Shariff, Roos Niza; Mohd Ali @ Ramli, Azlin Namili (2011)
This is one of the most popular legal battle cases for problematic contract terms. This paper will look into the unfair contract terms between JYJ and SME which were the main hiatus and the effects on Korean entertainers whom largely tied up with entertainment agency's contract.